The functionalism and the thesis of the social moratorium in the youth rebelliousnesse - Groppo, Luís Antonio (FCL-UNESP Laboratório Editorial, 2009)
A new critical analysis of the production of the functionalistic sociology about the youth reveals conceptions based on the idea of “normality”, something put as the calm adaptation between the youth condition and the social structure. The “abnormality” is interpreted as “dysfunctions” originated from the pernicious influence of “secret traditions” about the youth: bohemia, delinquency and radicalism. In the 1960’s, such interpretation is again considered, and a more generous view about the youth rebellions allows us to see them even as a possibility of reform and revolution of societies in crises, all through social progressive thinkers with arguments base don ideals of social transformation and citizenship, originating the thesis of the social moratorium.